Introducing comparative literature : new trends and applications - Domínguez, César (Routledge, 2015)
"Introducing Comparative Literature is a comprehensive guide to the field offering clear, concise information alongside useful analysis and examples. It frames the introduction within recent theoretical debates and shifts in the discipline whilst also addressing the history of the field and its practical application. Looking at Comparative Literature within the context of globalization, cosmopolitanism and post or transnationalism, the book also offers engagement and comparison with other visual media such as cinema and e-literature. The first four chapters address the broad theoretical issues within the field such as 'interliterary theory', decoloniality, and world literature, while the next four are more applied, looking at themes, translation, literary history and comparison with other arts. This engaging guide also contains a glossary of terms and concepts as well as a detailed guide to further reading"--